2021
DOI: 10.17135/jdhs.2021.21.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dental Hygienist Job Recognition Using Text Mining

Abstract: Background: The aim of this study was to analyze the public demand for information about the job of dental hygienists by mining text data collected from the online Q & A section on an Internet portal site. Methods: Text data were collected from inquiries that were posted on the Naver Q & A section from January 2003 to July 2020 using "dental hygienist job recognition," "role recognition," "medical assistance," and "scaling" as search keywords. Text mining techniques were used to identify significant Korean wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…The performance of dental insurance claims and "pati-ent reception" was also included in the high priorities of the two models. In Kim et al's study 13) , the frequency of business management support was the highest. In addition, the study by Hwang and Han 14) showed that the performance of patient reception and hospital management took up a considerably high frequency and required time.…”
Section: Comparison With Previous Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…The performance of dental insurance claims and "pati-ent reception" was also included in the high priorities of the two models. In Kim et al's study 13) , the frequency of business management support was the highest. In addition, the study by Hwang and Han 14) showed that the performance of patient reception and hospital management took up a considerably high frequency and required time.…”
Section: Comparison With Previous Studiesmentioning
confidence: 88%
“…It has been reported that there is a difference in the importance of the practice and that of the work recognized by dental hygienists when analyzing the importance of each treatment in the dental clinic. Kim et al 13) examined the frequency of duties performed by dental hygienists, the importance of duties as per dental hygienists, and the necessity of education, and presented them as basic data for the development of a curriculum corresponding to changes and demands of the times, expansion of duties of dental hygienists, and improvement of status. Additionally, to investigate the actual work of clinical dental hygienists, Hwang and Han 14) directly observed the frequency and time required for each treatment in the field and derived the improvement items to be included in the legal work by reflecting the actual work of the dental hygienist.…”
mentioning
confidence: 99%
“…If the researcher selects keywords arbitrarily, very biased research results can be derived in some cases, and the reliability of the research cannot be guaranteed. Therefore, existing literature that performed web crawling and text mining with a computer program was used for this study, to be as fair and objective as possible in selecting the keywords 10) .…”
Section: Abstract Selectionmentioning
confidence: 99%
“…상 임상적인 능력을 기르고자 노력하고 16) , 법적 가능 업무 등의 내용을 인지하는 데에도 시간을 아끼지 않고 있다 17) . 3년제 54개교, 4년제 28 개교에 이르는 국내 치위생학과에서도 전문성을 갖춘 치과위생사를…”
Section: 치과위생사들은 구강보건인력으로서의 역할에 충실하기 위해 항unclassified